Hotel Tua dan Ulasan Online Negatif: Apa Yang Dikatakan Pelanggan? - Ihwandi Ihwandi; Febrian Humaidi Sukmana (Magister Tourism Study, Faculty of Tourism, Udayana University, 2022)
The main purpose of this study was to find out what complaints were conveyed by customers through online reviews of one of the five-star resorts in Lombok. To find out, we conducted a content analysis of 314 negative reviews posted on the travel website TripAdvisor. To find out what complaints were conveyed by customers in their reviews, we used the JMP Pro14 software to analyze the datasets we had collected. Before presenting the main research findings (words/terms and phrases), this article provides an overview of some of the data elements that are an integral part of the main unit of analysis. For example, frequency distributions (ratings, reviewer contributions, word count, and length of stay), tables (including the reviewer's country of origin), and visualizations that compare the number of contributions and the rating given by a reviewer. The main result of this study found that the complaints on the three ratings in negative reviews were most often about